Evaluation of Structural Changes and Molecular Mechanism Induced by High Hydrostatic Pressure in Enterobacter sakazakii - Liao, Qiaoming; Tao, Han; Li, Yali; Xu, Yi; Wang, Hui-Li (Frontiers in Nutrition, 2021)
This study was to explore the inactivation mechanism of E. sakazakii induced by high hydrostatic pressure (HHP), a non-thermal technique for the pasteurisation and sterilization of dairy food. The mortality of E. sakazakii at 50 Mpa was 1.42 %, which was increased to 33.12 % at 400 Mpa. SEM and fluorescent staining showed that 400 Mpa led to a loss of physical integrity of cell membranes as manifested by more intracellular leakage of nucleic acid, intracellular protein and K+. RT-qPCR revealed that three functional genes (glpK, pbpC and ompR) related to cell membrane formation were significantly downregulated, indicating a lower level of glycerol utilization, outer membrane protein assembly and environmental tolerance. In addition, HHP modified the oxidative stress of E. sakazakii, as reflected by high activity of catalase and superoxide dismutase. HHP treatment downregulated the gene expression of flagellar proteins (fliC, flgI, fliH and flgK) and inhibited the biofilm formation.